Changes of serum miR-223-3p in patients with oral cancer treated with TPF regimen and the prognosis - Li, Chunru; Feng, Yao; Shao, Weiran (Oncology letters, 2020)
Changes of serum miR-223-3p in patients with oral cancer treated with TPF regimen and the prognosis were investigated. Fifty patients with oral cancer treated in the Affiliated Stomatological Hospital of Jiamusi University from March 2014 to January 2016 were enrolled in the study group, while 50 healthy subjects receiving physical examinations during the same period were enrolled in the control group. Serum expression of miR-223-3p was quantified by RT-qPCR. The diagnostic value of miR-223-3p in oral cancer was analyzed by the receiver operating characteristic (ROC) curve. Expression of miR-223-3p before and after treatment was compared. The study group was divided into the remission and the non-remission group based on the treatment outcome to analyze the predictive value of miR-223-3p. Patients were followed up for 3 years. Cox regression analysis was performed to analyze the independent prognostic factors. The relative serum miR-223-3p level was lower in the study than in the control group (P<0.001). Expression of miR-223-3p was significantly higher after treatment than before (P<0.05). Spearman's correlation analysis indicated that miR-223-3p expression before treatment gradually increased with the improvement of treatment outcome (r=0.617, P<0.001). The miR-223-3p level was markedly higher in the remission than in the non-remission group (P<0.05). The area under the ROC curve of miR-223-3p was 0.797. Multivariate Cox regression analysis demonstrated that the degree of differentiation [HR: 11.862 (95% CI: 2.730-51.547)] and miR-223-3p [HR: 3.489 (95% CI: 1.447-8.413)] were independent prognostic factors. The 3-year survival of patients with high differentiation and high miR-223-3p expression was significantly higher than that of patients with poor differentiation and low miR-223-3p expression (P<0.05). In conclusion, miR-223-3p expression is low in oral cancer, and it shows potential for predicting the efficacy and prognosis of patients with oral squamous cell carcinoma (OSCC) after TPF regimen.